2019
DOI: 10.1016/j.isci.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymers with Oligoethylene Glycol Side Chains for Improved Photocatalytic Hydrogen Evolution

Abstract: Summary Conjugated polymers are emerging as promising organic photocatalysts for hydrogen evolution from water. However, it is still very challenging for conjugated polymers to realize highly efficient photocatalytic hydrogen evolution. Herein, we demonstrate an efficient strategy of hydrophilic side chain functionalization to boost the hydrogen evolution rates of conjugated polymers. By functionalizing conjugated polymers with hydrophilic oligo (ethylene glycol) monomethyl ether (OEG) side chains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 54 publications
4
114
0
Order By: Relevance
“…Recent studies have shown that polymer hydrophilicity is an important factor in determining photocatalytic performance. [29][30][31][32] The incorporation of polar moieties such as dibenzo [b,d]thiophene sulfone 33 or nitrogen substituted benzenes 34 into the polymer backbone substantially improves the interaction with water. This in turn enhances the hydrogen evolution activity, partly by stabilizing the charge-separated state that is produced by hole transfer to the hole scavenger following photoexcitation of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that polymer hydrophilicity is an important factor in determining photocatalytic performance. [29][30][31][32] The incorporation of polar moieties such as dibenzo [b,d]thiophene sulfone 33 or nitrogen substituted benzenes 34 into the polymer backbone substantially improves the interaction with water. This in turn enhances the hydrogen evolution activity, partly by stabilizing the charge-separated state that is produced by hole transfer to the hole scavenger following photoexcitation of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…5 Conceptually, direct hydrogen production using photocatalyst suspensions is the simplest water-splitting approach in technological terms and it is potentially amenable to large-scale deployment. [7][8][9][10][11][12][13][14][15][16][17] Recently, several examples of photocatalysis has been reported as a one-step overall water splitting. [18][19][20] However, recombination of electron-hole pairs tends to decrease the photocatalytic reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[166] Introducing hydrophilic units increased polaron yields thanks to the organization of water around the polymer, whose polarity accelerated the electron transfer step. [166,167] Overall, the thermodynamic potentials for the redox reactions, the local environment and the driving forces for individual charge transfer steps are key factors to take into consideration when designing CPs for photocatalysts.…”
Section: Fuel Generation From An Aqueous Medium Via Photo or Electrocmentioning
confidence: 99%
“…[171] Hu et al synthesized conjugated backbones comprising a difluorobenzothiadiazole unit alongside a benzodithiophene unit functionalized with oligo ethylene glycol (OEG) side chains to boost photocatalytic performance. [167] The side chains improved the surface wettability with water, adsorbed protons and lowered the flat band potential, while interacting efficiently with the Pt co-catalyst. [172] The side chain engineering led to a dramatic 90-fold increase in the H 2 evolution rate compared to the alkyl analogue of the same backbone.…”
Section: Fuel Generation From An Aqueous Medium Via Photo or Electrocmentioning
confidence: 99%